Influencia de las habilidades visuales en el rendimiento y resultados de deportistas de tenis y tenis de mesa (2022)
Most methodologies in sports training have been developing exponentially in recent decades. Many resources and studies have been devoted to obtain important advances in this area, mainly focusing on visual functions.